GENITAL WARTS (CONDYLOMATA ACUMINATA): CURRENT PERSPECTIVES ON EPIDEMIOLOGY, DIAGNOSIS, TREATMENT AND PREVENTION. – A REVIEW - Julia Kosmulska; Anna Barbara Tuleja; Michał Drabik; Klaudia Dybalska; Maksym Sikora; Sylwia Wiktoria Kolano; Jakub Nowak; Michael Platschek; Mateusz Kęska; Karol Józef Szkarłat (International Journal of Innovative Technologies in Social Science, 2025)
Human papillomavirus (HPV) is the most prevalent sexually transmitted infection globally, responsible for a wide spectrum of epithelial lesions ranging from benign warts to invasive malignancies of the cervix, vulva, anus, and oropharynx. More than 200 genotypes have been identified, with low-risk types such as HPV-6 and HPV-11 linked to genital warts, andhigh-risk types, notably HPV-16 and HPV-18, associated with oncogenic transformation. Transmission occurs primarily through direct sexual contact, although nonsexual and vertical routes have been described. The majority of infections remain asymptomatic and transient, yet persistent infection with high-risk genotypes can lead to neoplastic progression. Diagnosisis mainly clinical, supported by histopathology and molecular HPV DNA detection when indicated. Current management focuses on lesion removal through topical agents (podophyllotoxin, imiquimod, sinecatechins) and ablative or surgical techniques, though recurrence remains frequent. Preventive strategies are central to disease control, with prophylactic HPV vaccination demonstrating remarkable efficacy in reducing infection rates and HPV-related disease burden worldwide. The bivalent, quadrivalent, and nonavalent vaccines provide durable protection for at least 10–14 years and are recommended before sexual debut. Expanding global vaccine coverage, combined with continued screening and education, remains vital to reducing HPV-related morbidity and mortality.